“I found my people”: Academic development, transformation and the Next Generation Professoriate at UCT - Morrell, R.; Patel, Z.; Jaga, A. (South African Journal of Higher Education, 2022)
Questions of inclusivity and transformation are central in higher education. In South Africa, these imperatives have the additional weight of post-apartheid redress. Attempts to address these questions seldom contemplate how transformation will be achieved. Efforts to achieve transformation often don’t attend to the critical question of how to nurture relationships among academics. We argue that building trust and a sense of belonging expands notions of academic development and transformation. In this article we discuss the Next Generation Professoriate (NGP), a mid-career academic development initiative at the University of Cape Town (UCT). Building human connections was an intentional part of this initiative’s transformative process. The programme emphasized global South location as a commonality as it sought to encourage new forms of knowledge production and collaboration.